Strategic Management, Branding and its Influence on Marketing: A Pending Subject? - Figueroa-Casillas, Sara J.; Rosario-Ruiz, María D. (EFIM Ediciones, 2021)
Strategically managing marketing decisions corresponds to one of the most important topics in the organizational aspect together with branding and the link with customers, however, the integration of these concepts is required. Thus, an analysis of the coverage provided by the academic literature on the aforementioned topics is proposed in order to promote a content analysis, where the importance of being more integrative in these aspects is highlighted. For these purposes, an analysis of the literature linking these topics is proposed, having as a finding that in practice they are discussed, analyzed and worked in the field with the business areas, with the purpose of shaping practical and clear tools to consolidate the strategic and marketing section in the organizations.